Un’eredità spinoziana. Questioni “postume”di spinozismo a partire dalle lettere di Pieter Van Gent a Tschirnhaus - EVANGELISTA, Roberto (Laboratorio dell'ISPF, 2014)
[An heritage of Spinoza’s. Some “posthumous” problems of spinozism through the letters of Pieter Van Gent to Tschirnhaus] Moving from the new book by Proietti and Licata about the correspondence between Van Gent and Tschirnhaus, this essay aims to point out some questions related to the early diffusion of Spinoza’s thought. In Van Gent’s letters some important problems that have already arisen in Spinoza’s correspondence with Schuller and Tschirnhaus come in light, including the nature of the attributes, the relationship between thought and matter and the immortality of soul. These issues show that materialism was one of the first interpretations of Spinoza’s philosophy.